Investigation of dynamic cable-deck interaction in a physical model of a cable-stayed bridge. Part I modal analysis. - Caetano, E. (Earthquake engineering & structural dynamics.)
A description of an experimental investigation involving the study of the dynamic interaction between the cables and the deck/towers.